Formation of Residual Bubbles in Diesel Engine Nozzle and Their Influence on Initial Jet. (12th August 2021) - Ni, Xiaonan; Wen, Hua
Abstract : The method of combining experiment and numerical simulation was used to study the cavitation and gas backflow phenomena during nozzle off-flow stage and the influence of residual bubbles on the initial jet in the near field. An equal-size optical nozzle based on acrylic material is designed, and the injection process of the fuel nozzle is photographed using high-speed photography technology. Establish a cavitation mathematical model to analyze the details of internal flow and initial jet. The results show that after the needle valve starts to close, cavitation occurs in the orifice and the sac in sequence, and the amount of cavitation in the sac is large. The collapse of cloud of cavitation bubbles will cause the outside air to flow back into the nozzle. The volume of the backflow air is slightly larger than the total volume of cloud of cavitation bubbles. The study found that the initial position of the residual bubbles has a significant effect on the initial atomization shape. When the residual bubble was in the front of the orifice, the initial tip was formed at the front of jet, and then, it stretched into a thin ligament due to vortex ring motion around the jet.